Knowledge modelling of CNC tool paths for function blocks - Ge, Xiaoli (Cranfield University, 2013)
Since the first CAPP (Computer Aided Process Planning) came out in the 1960’s, it has improved the performance of machining significantly. However, traditional process planning is established on the basis of a sequential information flow, which cannot easily be adapted to a dynamic manufacturing environment. DPP (Distributed Process Planning) was proposed for dynamic shop floor management for Function Blocks (Wang et al., 2003). Function Blocks, as described by the open standard IEC 61499, are used for distributed control and automation (International Electrotechnical Commission, 2005). The final goal of DPP is to develop an intelligent system which can respond to any event on shop floor rapidly and dynamically. The tool path, which determines the movement of a tool in machining operation, is an important part of process planning. In the past, a tool path was generated and used in a static manner (G-code), i.e. once created the path was not varied to adapt to major changes on the actual shop floor. As a result, it is essential to build a knowledge model that can adapt tool paths rapidly in a dynamic environment. The developed rules and recommendations can contributed to people who have less experience about NC tool path. Moreover, the research methodology could be used for other general research in knowledge capture and knowledge presentation.
Keywords: Tool path; Process planning; IEC 61499; Automatic control; Dynamic manufacturing environment; Knowledge modelling